Use of noninvasive mechanical ventilation for a bronchiolitis obliterans patient with respiratory failure [Solunum yetmezliǧi olan bir bronşiolitis obliterans vakasinda noninvaziv mekanik ventilasyon] - (:unkn) unknown (My University, 2004)
Bronchiolitis obliterans is characterized by persistent symptoms of obstructive lung disease after an acute bronchiolar injury. It is a rare disease in childhood occurring as a complication of mostly viral lower respiratory tract infections. There is limited information in the literature regarding the clinical course and treatment of children with bronchiolitis obliterans. In this case report, we present a 3.5-year-old boy who had an initial episode of bronciolitis at six months of age. He was treated with nebulized and systemic steroids and bronchodilators but required continuous hospitalization for the last five months. He had chronic respiratory failure and pulmonary hypertension when he was initially seen in our clinic at 2.5 years of age. His respiratory failure responded favorably to noninvasive ventilation via nasal mask and the patient was sent home on noninvasive ventilation during sleep. He required only one hospitalization during his one-year follow-up because of a viral infection-induced exacerbation. We were able to decrease his systemic steroid dose and his developmental parameters also improved after starting noninvasive ventilation. To our knowledge, this is the first report of the use of noninvasive ventilation in a child with bronchiolitis obliterans who has respiratory failure.
Keywords: Bronchiolitis obliterans; Noninvasive ventilation